Mastering Arabic Grammar with Contemporary Learning Method on Mohamed Mekawy’s Channel - Ramadhani, Nida Husnia; Mulyani, Rinda Eka; Fikri, Shofil; Nurhadi; Taha, Mohammed Adam Mohammed (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Learning nahwu (Arabic grammar) nowadays can be accessed on various digital platforms. One of them is Mohamed Mekawy's nahwu learning channel. Mohamed Mekawy provides nahwu learning materials and methods that anyone can master, from basic to advanced levels. Mekawy has an Arabic language learning institution called the Mekawy Academy, along with social media platform on YouTube, Instagram, TikTok, and Telegram. This study aims to understand the learning activity and the method used in nahwu learning from Mohamed Mekawy's social media. This study uses the Krippendorf analysis method with a qualitative approach that includes 6 research steps, those are determining the research theme, determining data sampling, finding answers to the research questions, filtering the data, connecting the findings, and writing the research report. The results of the study show that Mekawy has a distinctive method in mastering nahwu, first is the choice of starting material by mu'rab and mabni or al-jumlah al-fi'liyyah and al-jumlah al-ismiyyah. Second are Maharah tafkīk which is the skill of breaking down a sentence into individual words and maharah taṣnif which is the skill of classifying words into isim, fi`il, or ḥarf. The last or third is the application of the analogy method. This research will provide new ideas in studying nahwu with new methods up to an advanced level. A recommended topic for future research is the creation of short videos to facilitate understanding of nahwu on social media, which can be studied using the research and development method to create the idea of using social media as media to learn nahwu.